Measurement-Based Cellular Band Air-to-Ground Channel Modeling for UAVs - Erkek, Necati Kagan; Balci, Emre; Halay, Berkin; Erdemir, Ubeydullah; Gorcin, Ali; Cirpan, Hakan Ali (IEEE, 2022)
Unmanned aerial vehicles (UAVs) play a critical role in the fifth-generation and beyond communications. Since UAVs have an important potential in terms of getting deployed as base stations in next generation wireless networks, an extensive elaboration is required to model UAV wireless communication channels both in terms of large-scale and small-scale characteristics. To this end, the main objective of this study is to reveal alterations of air-to-ground wireless propagation channels for possible base station allocation at the height of 50 m, based on real measurements. The large-scale characteristics of the channel are analyzed by log-distance path loss model and the flat earth two-ray model. The small-scale characteristics of the propagation channel are examined considering the Rician K factor and root mean square delay spread. The measurement results also include channel impulse response and power delay profile results make it possible to observe the multi-path components on the wireless communication channel. The measurement campaign is conducted in a setting of hilly terrain layout at 2.57 GHz which is one of the 5G mid-band frequencies.
Keywords: UAV; Air to Ground Channel; Path Loss; FE2R; Power Delay Profile; RMS Delay Spread; Software Defined Radio; Engineering; Telecommunications; Transportation